THE ROLE OF THE SCHOOL HEAD IN THE SELF-DEVELOPMENT OF STUDENTS THROUGH EXTRACULAR ACTIVITIES (CASE STUDY MIN 1 BENER MERIAH) - Tiarani Mirela; Na'imah Na'imah; Lailatussaadah Lailatussaadah (JURNAL ILMIAH DIDAKTIKA: Media Ilmiah Pendidikan dan Pengajaran, 2022)
The purpose of this study was to describe why the role of the principal in self-development of students through extracurricular activities at MIN 1 Bener Meriah, and to describe the role of  the principal in self-development of students through extracurricular activities at MIN 1 Bener Meriah. This study is a qualitative type using observational, interviews and documentation, data analysis using triangulation theory. Based on the results of the research: the role of the principal is very important in the self-development of students at MIN 1 Bener Meriah. Among these roles are (1) educator: teaching with teacher intermediaries, (2) manager: managing with POAC even though the field is narrow, (3) administrators: take care of correspondence and funding for extracurricular activities, (4) supervise extracurricular activities through joint meetings and direct involvement, (5) leaders: mobilize involved teachers and students in extracurricular activities, (6) innovator: Principals make reforms such as creative guel dance (7) motivator: the principal provides encouragement in the form of words and gifts for students who excel, including in extracurricular activities. So that the role of the principal is done well, it will also have a good impact on the development of students in the extracurricular program.